Пошаговое объяснение:
a) - 5(-2)×(-30):12=10×(-2,5)= - 25
в) (-12-6+30):(-4)=12:(-4)= - 3
д) - 125:(-12+7):(-10)= - 125:(-5):(-10)=25:(-10)=
= - 2,5
б) 11(-6):(-3):(-1)= - 66:(-3):(-1)=22:(-1)= - 22
г) (6-12):(-2+8)= - 6:6= - 1
е) - 1000:125-(-5+9)= - 8-4= - 12
1 см² = 1 см * 1 см = 10 мм * 10 мм = 100 мм²
1 дм² = 1 дм * 1 дм = 10 см * 10 см = 100 см²
5 см² 40 мм² + 18 см² = (5 * 100 + 40) мм² + (18 * 100) мм² =
= 540 мм² + 1800 мм² = 2340 мм² = 23 см² 40 мм² = 23,40 см²
12 см² 40 мм² + 60 мм² = (12 * 100 + 40) мм² + 60 мм² =
= 1240 мм² + 60 мм² = 1300 мм² = 13 см²
8 дм² 34 см² - 44 см² = (8 * 100 + 34) см² - 44 см² =
= 834 см² - 44 см² = 790 см² = 7 дм² 90 см² = 7,9 дм²
Задание 2.a = 43 м
P = 172 м
P = (a + b) * 2
a + b = P/2
b = P/2 - a
b = 172/2 - 43
b = 43 м
S = a * b
S = 43 * 43
S = 1849 м²
b = 20 м
P = 110 м
a = P/2 - b
a = 110/2 - 20
a = 35 м
S = a * b
S = 35 * 20
S = 700 м²
1 см² = 1 см * 1 см = 10 мм * 10 мм = 100 мм²
1 дм² = 1 дм * 1 дм = 10 см * 10 см = 100 см²
5 см² 40 мм² + 18 см² = (5 * 100 + 40) мм² + (18 * 100) мм² =
= 540 мм² + 1800 мм² = 2340 мм² = 23 см² 40 мм² = 23,40 см²
12 см² 40 мм² + 60 мм² = (12 * 100 + 40) мм² + 60 мм² =
= 1240 мм² + 60 мм² = 1300 мм² = 13 см²
8 дм² 34 см² - 44 см² = (8 * 100 + 34) см² - 44 см² =
= 834 см² - 44 см² = 790 см² = 7 дм² 90 см² = 7,9 дм²
Задание 2.a = 43 м
P = 172 м
P = (a + b) * 2
a + b = P/2
b = P/2 - a
b = 172/2 - 43
b = 43 м
S = a * b
S = 43 * 43
S = 1849 м²
b = 20 м
P = 110 м
a = P/2 - b
a = 110/2 - 20
a = 35 м
S = a * b
S = 35 * 20
S = 700 м²
Пошаговое объяснение:
А) -25
в)-3
Д)-2,5
Б)-2
Г)-1
Е)?